PROCESS AND RELATIONSHIP IN INDIGENOUS ASTRONOMY: CONNECTIVITY OF MOTHER EARTH AND FATHER SKY - Nancy C. Maryboy (Unmas Press, 2020)
Many people around the world still live in accordance with a world view that is remarkably different from the Euro-American world view. This paper discusses some of the striking differences between western academic science and Indigenous ways of knowing. Beginning with the original meaning of the word “science” the paper focuses on the importance of world view and cultural outlook as a framework for understanding the world. Much of the complex Indigenous world view is contained in the original Indigenous languages, which are relational and process oriented, very different from European languages which are noun-centric and non-relational. Many Asian languages, such as Chinese, are constructed in ways similar to Indigenous (in this case Navajo) languages. The work of quantum physicist David Bohm comes closest to Navajo (and Blackfoot) ways of knowing, with his work on the existence of an explicate and an implicate world, existing in ceaseless movement, called holomovement. Indigenous astronomy is positioned in a world view of interconnection and interrelationship of all things. Everything is living and animate in a universe of cosmic movement. This relational way of viewing the universe has major implications for understanding the way a world view impacts and constructs astronomy and cosmology of a people.